Analysis of precipitation in Bakony mountains - Fogarasi Sándor (2001)
This paper presents the results of the research, which has analysed the precipitation of Bakony Mountains (part of Transdanubian karst system) between 1991 and 1995. At the same time we have studied the infdtration too. The first step was to study the temporal distribution of the heavy amount of precipitation (occurrence, intensity, macrosynoptic situations). Based on these data we have concluded, that the precipitation in this area is concentrated. As the next step of the investigation we have determined the causes of the increased amount of mean precipitation of the first half of 1990's. We could easily separate these in the studied period. It seems that this increase of precipitation is a part of a trend. By the the study we can conclude, that in the regeneration of karstwater-system of the Transdanubian Mountains not only the increasing of amount of precipitation played an important role, but the change of its temporal distribution too. The causes of this increase of precipitation were compared with macrosynoptic situations.
Keywords: Természettudományok; Föld- és kapcsolódó környezettudományok